Omnibus Method in National Legal Development Efforts - Putri Aji, Rizka Ananda; Susilawati, Elis (Nurani, 2023)
Pancasila is the view of life of the nation and state which is the basis for the implementation of national life. The precepts in "Pancasila" are the crystallization of the values​​that live in Indonesian society. This is certainly a new thing in the Indonesian legal system which is more inclined towards the civil law system. The omnibus concept is better known in countries with a common law system. However, as stated by Mochtar Kusumaatmadja thatin efforts to develop law there must be alignment between the national legal system and the development of modern law from other countries. This alignment is solely intended so that the law can adapt to the times.The method used in this research is the normative legal method. -Invitation” which accommodates the omnibus method. This method is an effective and efficient effort to overcome regulatory obesity that occurs in Indonesia. However, in its implementation, future improvements are needed to achieve the target to be achieved.